Proliferative capacity of mouse peritoneal macrophages in vitro (The Rockefeller University Press, 1978)
Thioglycolate-stimulated mouse peritoneal macrophages cultured in the presence of macrophage growth factor (MGF) will continue to proliferate when they are removed from culture dishes with the local anesthetic lidocaine and subcultured. The number of times the cells can be subcultured and remain in a proliferative state is dependent on the number of previous cell divisions. One precursor cell (colony-forming cell) yields about 2.6 X 10(4) daughter cells. When MGF is removed from actively proliferating macrophages, they leave the cell cycle and enter a "resting" condition. When MGF is readded, cells reenter the cell cycle and proliferate with the same doubling time as if MGF had not been removed. Membrane 5'-nucleotidase activity was used as a probe to identify the state of macrophage activation. Proliferating macrophage populations had significantly higher enzyme levels than stimulated macrophages cultured without MGF. These enzymes levels were, however, lower than those found for resident (unstimulated) macrophages.